Comparative differential scanning calorimetric analysis of vegetable oils: I. Effects of heating rate variation - Tan, C. P.; Che Man, Y. B. (Wiley, 2002)
The melting curves of 11 vegetable oils have been characterised. Vegetable oil samples that were cooled at a constant rate (5°C/min) from the melt showed between one and seven melting endotherms upon heating at four different heating rates (1, 5, 10 and 20°C/min) in a differential scanning calorimeter (DSC). Triacylglycerol (TAG) profiles and iodine value analyses were used to complement the DSC data. Generally, the melting transition temperature shifted to higher values with increased rates of heating. The breadth of the melting endotherm and the area under the melting peak also increased with increasing heating rate. Although the number of endothermic peaks was dependent on heating rate, the melting curves of the oil samples were not straightforward in that there was no correlation between the number of endothermic peaks and heating rates. Multiple melting behaviour in DSC experiments with different heating rates could be explained by: (1) the melting of TAG populations with different melting points; and (2) TAG crystal reorganisation effects. On the basis of the corollary results obtained, vegetable oils and fats may be distinguished from their offset-temperature (Toff) values in the DSC melting curves. The results showed that Toff values of all oil samples were significantly (p < 0.01) different in the melting curves scanned at four different scanning rates. These calorimetric results indicate that DSC is a valuable technique for studying vegetable oils